Education in Interventional Pulmonology: How We Got Here and Where to Go from Here - Dylan Harrell; David M. Chambers (MDPI AG, 2024)
Interventional pulmonology is a rapidly growing field with increasing demand. To meet this demand, training in interventional pulmonology is expanding. What started as a single training program without a standardized curriculum has grown to 40 accredited training programs with a well-defined curriculum that is now overseen by the Accreditation Council for Graduate Medical Education. As the field develops, research is being actively performed to develop validated competency assessment tools and describe the learning curves for pulmonary procedures. As research evolves, this information can be used to better standardize training in interventional pulmonology and move the field towards a competency-based training model.